The Effect of Financial Literacy, and Lifestyle on Individual Financial Management of Employees at Paulus Indonesian Christian University - Sabandar, Sita; Udang , Yunita Restan; Gunadi, Hendrik (PT. Maju Malaqbi Makkarana, 2025)
This research aims to determine the impact of Financial Literacy and Lifestyle on the individual financial management of employees at Paulus Indonesian Christian University. The problem focuses on identifying financial literacy and lifestyle that play a role in managing the personal finances of Paulus Indonesian Christian University employees. The associative and comparative methods are used in problem formulation and hypothesis. This quantitative research uses a saturated sampling technique, namely all people are sampled, where the sample size is 65 people or all employees of the Indonesian Paulus Christian University. Data was collected through questionnaires and analysed quantitatively with the Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, t-test, and f-test. The results of the hypothesis test show that financial literacy has a significant positive effect on individual financial management, while lifestyle has a non-significant and negative effect on personal management. Although Lifestyle has an insignificant and negative effect, together with Financial Literacy it is stated that it has a significant positive effect on Individual Financial Management for UKI Paulus employees